Relevansi Model Konstruksivisme Jean Piaget Bagi Pengembangan Pendidikan Agama Islam (PAI) - Anwar Dhobith; Usman; Sibawaihi (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This article aims to examine the application of Jean Piaget’s constructivist methodology in the development of Islamic Religious Education (PAI). Using a qualitative approach through library research, this study explores the epistemological and ontological framework of Piaget’s constructivism, which emphasizes that learners actively construct knowledge through interaction with their environment and cognitive developmental stages. The application of this approach in PAI includes gradual and contextual material development, interactive and experience-based learning methods, and the teacher’s role as a facilitator. The findings indicate that Piaget’s constructivism positively contributes to a more meaningful, critical, and reflective PAI learning process. However, challenges remain, including age limitations of the theory, potential misinterpretations, and the lack of integration of spiritual dimensions. Therefore, methodological adjustments are necessary to effectively implement this theory within the holistic context of Islamic education.